Analysis and Design Of Web-Based Catering Ordering Systems (Case Study: Cafetaria Catering) - Fery Abdul Pradana (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2021)
Along with the development of technological advancements and high business competition in the field of catering, Catering Cafetaria needs to use a website for promotional facilities to develop its business or as a marketing tool to increase sales. The development of information technology used in the catering world can use webservice for interoperability, with features such as wifi, sms gateway, and the use of mobile applications with android can be a reference for further development. As for the design of the system used UML and the Waterfall method. The ordering process for catering to Catering Cafes is still manual, so it often creates obstacles and is considered less effective and efficient in ordering. A web-based catering service ordering information system is needed to overcome this problem. This ordering system is also considered to be more efficient in utilizing and reducing costs for marketing. The design of this catering-based ordering system is made using PHP and MySQL. The benefits of this research are to help Catering Cafetaria to facilitate expenses, online catering reservations and for computerized business progress.